LYDDA FRANCO FARIAS: UNA VOZ QUE NO CALLA (De la Crítica, 2023)
The present essay has as purpose investigate the sources that feed the imaginary of the falconian poet Lydda Franco Farías, considered one of the female voices most outstanding of Venezuelan poetry, through the opinions expressed by scholars of his poetic ars. An approach is al so made of the theme that the autor handles in published poems, in search of literary signs that lead to the points of origin in his extensive´poetry.